REPRESENTASI RASISME PADA FILM “12 YEARS A SLAVE” (Analisis Semiotika Roland Barthes) - Ricky Wirianto; Lasmery Rosentauly Meissalinya Girsang (SEMIOTIKA: Jurnal Komunikasi, 2016)
Film has been a need for society, not only as entertainment tool, but also as education tool that sets social values up among society. Including “12 Years A Slave” film which describes slavery in racism issue. All symbols and attributes in this film are necessarily explored to understand slavery reality in United States of America at that era. This qualitative research is subjective-interpretive using semiotic analysis, namely two orders from Roland Barthes. Researcher chooses sampling from selected scenes related to racism issues. For the results, there are four representations of racism, namely: (1) White people dominates the black people, (2) White people is hero for black people, (3) Black people is the incarnation of devil, and (4) Black people is set up for working, not for academic. Keywords: Racism, Representation, Film, Semiotics, Roland Barthes